Ecdysteroids: A novel class of anabolic agents? - Parr, MK; Botrè, F; Naß, A; Hengevoss, J; Diel, P (Biology of Sport, 2015)
Increasing numbers of dietary supplements with ecdysteroids are marketed as “natural anabolic agents”. Results of recent studies suggested that their anabolic effect is mediated by estrogen receptor (ER) binding. Within this study the anabolic potency of ecdysterone was compared to well characterized anabolic substances. Effects on the fiber sizes of the soleus muscle in rats as well the diameter of C2C12 derived myotubes were used as biological readouts. Ecdysterone exhibited a strong hypertrophic effect on the fiber size of rat soleus muscle that was found even stronger compared to the test compounds metandienone (dianabol), estradienedione (trenbolox), and SARM S 1, all administered in the same dose (5 mg/kg body weight, for 21 days). In C2C12 myotubes ecdysterone (1 μM) induced a significant increase of the diameter comparable to dihydrotestosterone (1 μM) and IGF 1 (1.3 nM). Molecular docking experiments supported the ERβ mediated action of ecdysterone. To clarify its status in sports, ecdysterone should be considered to be included in the class “S1.2 Other Anabolic Agents” of the list of prohibited substances of the World Anti-Doping Agency.